Generalized, focal, and combined epilepsies in families: New evidence for distinct genetic factors. (23rd October 2020) - Ellis, Colin A.; Ottman, Ruth; Epstein, Michael P.; Berkovic, Samuel F.
Abstract: Objective: To determine the roles of shared and distinct genetic influences on generalized and focal epilepsy operating in individuals who manifest features of both types ( combined epilepsies ), and in families manifesting both generalized and focal epilepsies in separate individuals ( mixed families ). Methods: We analyzed the deeply phenotyped Epi4K cohort of multiplex families (≥3 affected individuals per family) using methods that quantify the aggregation of phenotypes within families and the relatedness of individuals with different phenotypes within family pedigrees. Results: The cohort included 281 families containing 1021 individuals with generalized (n = 484), focal (304), combined (51), or unclassified (182) epilepsies. The odds of combined epilepsy was higher in relatives of participants with combined epilepsy than in relatives of those with other epilepsy types (odds ratio [OR] 5.2, 95% confidence interval [CI] 1.7‐16.1, P = .004). Individuals with combined epilepsy co‐occurred in families more often than expected by chance ( P = .03). Within mixed families, individuals with each type of epilepsy were more closely related to relatives with the same type than to relatives with other types ( P < .001). Significance: These findings suggest that distinct genetic influences underlie the recently recognized entity of combined epilepsies, just as generalized epilepsies and focal epilepsies each have distinct genetic influences. Mixed families may in part reflect chance co‐occurrence of these distinct genetic influences. These conclusions have important implications for molecular genetic studies aimed at identifying genetic determinants of the epilepsies.